1982
DOI: 10.1007/bf00294968
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal arrangement of heat shock locus 2-48B in Drosophila hydei

Abstract: cDNA, copied from nuclear RNA isolated from heat shocked Drosophila hydei cells, has been cloned. From this collection of clones a clone, N09-15, with a 450 bp insert has been isolated that hybridizes in situ to the heat shock locus-2-48B of Drosophila hydei. The N09-15 sequence is present in two different genomic arrangements, as shown by restriction mapping, in our wild type D. hydei population. These genomic arrangements are allelic. Both alleles contain multiple copies of the N09-15 sequence but differ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This is also supported by earlier data: all three puffs can be induced independently of the other heat-shock puffs (Lakhotia 1749 Heat-shock puff 93 D of D. melanogaster and Mukherjee, 1970Mukherjee, , 1980Leenders et al, 1973;Bonner and Pardue, 1976;Gubenko and Barisheva, 1979;Lakhotia and Singh, 1982); 93 D and 48 B map close to the ebony locus (D'Alessandro et al, 1977;Henikoff, 1980;Grond et al, 1982) and produce a RNA that remains largely in the nucleus and is unlikely to code for a protein (Lengyel et al, 1980;Lubsen et al, 1978;Peters et al, 1982). These similarities of the described loci are, however, not paralleled by conservation at the level of primary DNA structure (Peters et al, 1980(Peters et al, , 1982. Interestingly, the protein recognized by the P11 antibody also appears to have changed during evolution, as indicated by the lack of cross-reactivity of the P11 antibody (in addition to Q14 and Q16 which also belong to the P11 group) with D. hydei and D. virilis chromosomes (Saumweber et al, 1980).…”
Section: Discussionsupporting
confidence: 81%
“…This is also supported by earlier data: all three puffs can be induced independently of the other heat-shock puffs (Lakhotia 1749 Heat-shock puff 93 D of D. melanogaster and Mukherjee, 1970Mukherjee, , 1980Leenders et al, 1973;Bonner and Pardue, 1976;Gubenko and Barisheva, 1979;Lakhotia and Singh, 1982); 93 D and 48 B map close to the ebony locus (D'Alessandro et al, 1977;Henikoff, 1980;Grond et al, 1982) and produce a RNA that remains largely in the nucleus and is unlikely to code for a protein (Lengyel et al, 1980;Lubsen et al, 1978;Peters et al, 1982). These similarities of the described loci are, however, not paralleled by conservation at the level of primary DNA structure (Peters et al, 1980(Peters et al, , 1982. Interestingly, the protein recognized by the P11 antibody also appears to have changed during evolution, as indicated by the lack of cross-reactivity of the P11 antibody (in addition to Q14 and Q16 which also belong to the P11 group) with D. hydei and D. virilis chromosomes (Saumweber et al, 1980).…”
Section: Discussionsupporting
confidence: 81%
“…The tandem repeats uniquely associated with the hsrω gene in D. mel have attracted considerable attention due to their specific association with the omega speckles (Lakhotia, 2011;Prasanth, et al, 2000;Singh and Lakhotia, 2015). Interestingly, the initial cloning and sequencing of the hsrω gene from three species in the 1980s Peters, et al, 1982;Peters, et al, 1984;Ryseck, et al, 1987) indicated the repeats to be the most variable component of this gene. The present bioinformatic analysis also revealed that the hsrω gene associated repeats were the most variable component in spite of their being unique to this gene.…”
Section: Discussionmentioning
confidence: 99%
“…Following the advent of genome sequencing, the hsrω gene has been annotated in 12 Drosophila species at the FlyBase (http://flybase.org/cgi-bin/gbrowse2/) while unannotated genome sequences of many more species are available at the NCBI database (https://www.ncbi.nlm.nih.gov/). Based on the early studies (Lakhotia, 2011;Peters, et al, 1982), it appeared that this gene had common architectural features with ~10 to 15kb long transcription unit, whose proximal part (~2.6kb) comprised of unique sequence while the distal region (>5kb) contained tandem repeats of a short sequence, unique to this locus Peters, et al, 1982;Peters, et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding heat-shock locus from D. hydei (Peters et al, 1982(Peters et al, , 1984 also contains an internally-repetitive structure and the RNA transcribed after heat shock derives from the repetitive and flanking unique part of the DNA. Although the repeat structure cloned from D. hydei showed no apparent cross-hybridization to the TaqI repeat of heat-shock locus 93D the similarity in the overall structure of small repeat units clustered over several kb in length is astonishing.…”
Section: Discussionmentioning
confidence: 99%